2022
DOI: 10.48550/arxiv.2203.05442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conics on Gushel-Mukai fourfolds, EPW sextics and Bridgeland moduli spaces

Abstract: We identify the double dual EPW sextic Y A ⊥ and the double EPW sextic Y A , associated with a very general Gushel-Mukai fourfold X, with the Bridgeland moduli spaces of stable objects of character Λ 1 and Λ 2 in the Kuznetsov component Ku(X). This provides an affirmative answer to a question of Perry-Pertusi-Zhao. As an application, we prove a conjecture of Kuznetsov-Perry for very general Gushel-Mukai fourfolds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…This is not proven in [31]; what is known [31,Proposition 5.17] is that either the two maps agree, or the modular construction gives the double EPW sextic that is dual to the Iliev-Manivel construction. (For completeness, we should mention the recent work [20], where it is shown that ν P P Z actually agrees with ν.) Either way, the morphism ν P P Z : M • GM 4 → M dEP W is dominant.…”
Section: 2mentioning
confidence: 82%
“…This is not proven in [31]; what is known [31,Proposition 5.17] is that either the two maps agree, or the modular construction gives the double EPW sextic that is dual to the Iliev-Manivel construction. (For completeness, we should mention the recent work [20], where it is shown that ν P P Z actually agrees with ν.) Either way, the morphism ν P P Z : M • GM 4 → M dEP W is dominant.…”
Section: 2mentioning
confidence: 82%
“…In [26], the authors generalize Theorem 9.2 to all prime Fano threefolds of genus g ⩾ 6. In [18], the authors prove a birational categorical Torelli theorem for general non-Hodge-special Gushel-Mukai fourfolds.…”
Section: Categorical Torelli Theoremsmentioning
confidence: 99%